PENGARUH STRUKTUR MODAL TERHADAP KINERJA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 - Novita Mardyani Rosalinawati; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2015)
This  study  aims  to  empirically  examine  the  impact  of  capital  structure  on  performance  of companies in Indonesia, which is one of developing countries. Dependent variable of this study is the performance of the company. Performance is measured by Return on Asset (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Independent variable is debt level as a proxy of capital structure. Debt level is measured by the ratio of short-term debt to total asset (STD), ratio of long-term debt total asset (LTD), and ratio of total debt to total asset (TTD). In addition, this study also use firm size as control variable. Population in this study includes all companies listed in  Indonesia Stock  Exchange  (IDX) in 2013. Selection of the sample is done  with  purposive sampling method. Sample used in this study are all non-financial companies that have financial data availability in 2013 and have positive equity value. Initial sample obtained are 393 data. After excluding 13 outlierS, the final sampel used in this study are 380 data. Multiple regression analysis is utilized for hypotheses testing. Overall, the results show that capital structure has significant negative effects on the company performance variables. STD, LTD, and TTD have negative effects on ROA. LTD and TTD have negative effect on ROE, whereas the effect of STD on ROE is not significant. Furthermore, STD and TTD also negatively affect NPM, while the influence of the LTD on NPM is not significant.